Kiklewicz, Aleksander (2021) Lingwistyka na bieżąco. Wypisy i komentarze Lublin: Episteme; pp. 277 - Giwojno, Paweł (2022)
The author of the reviewed book skillfully interconnects two linguistics components, namely interesting extractsfrom the corpus of contemporary Polish, as well as professional and substantive linguistic analyses, both of whichmake this book a perfect popular–scientific compendium. This well thought–out combination of the above–mentioned components undoubtedly makes Professor Kiklewicz’s work an excellent introduction to the broaddomain of contemporary linguistic studies, as well as a vivid illustration of changes noticed in contemporary Polish.As such, it fits perfectly to the trend of popularizing knowledge about the contemporary Polish language.
Keywords: Kiklewicz, Aleksander